rbcL and rpoL gene sequences of Panax vietnamensis var. fuscidiscus and Panax vietnamensis, the background for identification and comparison - Phuong Trang, Nguyen Thi; Hong Mai, Nguyen Thi; Yury N, Zhuravlev; Galina D, Reunova (Academia Journal of Biology, 2016)
The Panax vietnamensis var. fuscidiscus samples collected at Phong Tho district, Lai Chau Province have morphological characteristics very similar with those of Panax vietnamensis distributed in Ngoc Linh mountain at Quang Nam and Kon Tum provinces that hinders the identification of these taxons. To supply the information to identify two species and know the genetic distance of these species with other Panax species, we sequenced rbcL and rpoB genes that are among DNA barcoding markers recommended for plant species identification. In the rbcL gene of 700 bp in length, we found 9 nucleotide differences between Panax vietnamensis var. fuscidiscus and Panax vietnamensis and the genetic similarity was 98,8%, while in the rpoB gene of 500 bp in length, only 2 nucleotide differences were discovered and the genetic distance was 0,4%. The sequences of rbcL and rpoB of Panax vietnamensis var. fuscidiscus and Panax vietnamensis were submitted to Genbank with the accession numbers KT194325.1, KT194324.1 and KT154685.1, KT154686.1 respectively.   Citation: Nguyen Thi Phuong Trang, Nguyen Thi Hong Mai, Zhuravlev Yury N., Reunova Galina D., 2017. rbcL and rpoB gene sequences of Panax vietnamensis var. fuscidiscus and panax vietnamensis, the background for identification and comparison. Tap chi Sinh hoc, 39(1): 80-85. DOI: 10.15625/0866-7160/v39n1.7870 *Corresponding author: ntptrang@yahoo.com. Received 11 March 2016, accepted 20 March 2017